WISE-Energy: Wireless Integrated Smart Energy Systems - Ichwana Putra, Dody; Ekariani, Shelvi (AI Society & STMIK Indonesia, 2024)
This paper introduces WISE-Engergy, Wireless Integrated Smart Energi Systems. This system is designed to optimize indoor electricity usage by fostering user awareness of energy-saving practices. Users are reminded to turn off electrical devices when leaving the room through notifications on an Android smartphone application. The research aims to increase public awareness of the importance of energy conservation and to apply technology to achieve higher energy efficiency. The contribution of this research lies in the development of an innovative energy-saving system that can be implemented in various indoor environments to support sustainable energy-saving efforts. The test results show that this system successfully achieves its intended goals. The notifications sent to the last user in the room effectively encouraged them to turn off the lights upon leaving. The WSN communication test between room 1 and room 2 also demonstrated that the system could transmit power data from room 2 to room 1 via the XBee module. System evaluation and testing indicated that SENIOR successfully notified users to turn off electrical devices. This research makes a significant contribution to addressing energy-saving challenges and promoting an energy-saving culture in the community.